CAGE-miR-140-5p-Wnt1 Axis Regulates Autophagic Flux, Tumorigenic Potential of Mouse Colon Cancer Cells and Cellular Interactions Mediated by Exosomes - Yeon, Minjeong; Lee, Seungheon; Lee, Joo-Eun; Jung, Hyun Suk; Kim, Youngmi; Jeoung, Dooil (Frontiers in Oncology, 2019)
Although the cancer/testis antigen CAGE has been implicated in tumorigenesis, the molecular mechanisms of CAGE-promoted tumorigenesis remain largely unknown. CT26Flag−CAGE cells, CT26 (mouse colon cancer cells) cells stably expressing CAGE, were established to investigate CAGE-promoted tumorigenesis. Down-regulation of CAGE led to decreased autophagic flux in CT26Flag−CAGE cells. CAGE interacted with Beclin1, a mediator of autophagy. The CT26Flag−CAGE cells showed enhanced autophagosome formation and displayed greater tumor spheroid-forming potential than CT26 cells. MicroRNA array analysis revealed that CAGE decreased the expression of various microRNAs, including miR-140-5p, in CT26 cells. CAGE was shown to bind to the promoter sequences of miR-140-5p. MiR-140-5p inhibition increased the tumorigenic potential of and autophagic flux in CT26 cells. A miR-140-5p mimic exerted negative effects on the tumorigenic potential of CT26Flag−CAGE cells and autophagic flux in CT26Flag−CAGE cells. MiR-140-5p was predicted to bind to the 3′-UTR of Wnt1. CT26Flag−CAGE cells showed higher expression of Wnt1 than CT26 cells. Down-regulation of Wnt1 decreased autophagic flux. Luciferase activity assays showed the direct regulation of wnt1 by miR-140-5p. Tumor tissue derived from the CT26Flag−CAGE cells revealed higher expressions of factors associated with activated mast cells and tumor-associated macrophages than tumor tissue derived from CT26 cells. Culture medium from the CT26Flag−CAGE cells increased autophagic flux in CT26 cells, mast cells and macrophages. Culture medium from the CT26Flag−CAGE cells increased CD163 and autophagic flux in CT26 cells, mast cells, and macrophages in a Wnt1-dependent manner. Exosomes from CT26Flag−CAGE cells increased autophagc flux in CT26 cells, mast cells, and macrophages. Exosomes from CT26Flag−CAGE cells increased the tumorigenic potential of CT26 cells. Wnt1 was shown to be present within the exosomes. Recombinant Wnt1 protein increased autophagic flux in CT26, mast cells, and macrophages. Recombinant wnt1 protein mediated interactions between the CT26 cells, mast cells, and macrophages. Our results showed novel roles for the CAGE-miR-140-5p-Wnt1 axis in autophagic flux and cellular interactions mediated by exosomes.